Léčba impingement syndromu ramena pomocí injekce PRP - Šmíd, P; Hart, R; Komzák, M; Paša, L; Puskeiler, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2018)
PURPOSE OF THE STUDY This study aimed to explore the effects of new therapeutic procedures in patients with shoulder impingement syndrome. The primary goal of the study was to confirm the hypothesis that the application of the platelet-rich plasma (PRP) in patients with shoulder impingement syndrome will have a positive effect on both the subjective and objective evaluation of their condition. The clinical condition before and after the treatment was evaluated. The secondary goal was to compare the effect achieved by a series of 3 PRP injections and that achieved by treating the impingement syndrome with a standard single depot corticosteroid injection. MATERIAL AND METHODS The randomized prospective blinded study carried out in the period 2013-2015 included 25 patients (Group I), to whom 3 PRP injections were applied in the subacromial (SA) space at a 1-week interval at the outpatient department. The control group of 25 patients (Group II) was treated by a standard single depot corticosteroid injection applied in the SA space. The subjective and objective conditions were evaluated immediately before the treatment, at 6 weeks, 3 months and 6 months after the administration of the injection. The evaluation comprised a physical examination, an evaluation using the Visual Analogue Scale (VAS), ASES (American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form) and the Constant score. A part of the study was the statistical processing of the results. RESULTS Both the groups were comparable when assessing the mean age of patients as well as the share of both sexes in the groups; Group I with the mean age of 48.7 years (15 men and 10 women), Group II with the mean age of 50.1 years (16 men and 9 women), but also when assessing the baseline mean VAS score, Constant score and ASES score. In Group I, the baseline mean VAS score improved from 2.96 (range: 1-5; median: 3.0; SD: 0.77) to 2.0 (range: 1-3; median: 2.0; SD: 0.49) at 3 months after the administration and to the mean value of 1.16 (range: 0-2; median: 1.0; SO: 0.67) at 6 months after the last PRP injection. In Group II, the baseline mean VAS score improved from 3.12 (range: 2-5; median: 3.0; SD: 0.82) to the mean value of 2.16 (range: 1-4; median: 2.0; SD: 0.73) at 3 months after the administration of the depot corticosteroid injection and to 1.8 (range: 1-3; median: 2.0; SD: 0.57) at 6 months after the administration. In both the groups of patients, the p-value obtained by the Student s t-test was statistically significant (p < 0.05) when comparing the results of all the three scoring systems before the treatment and 6 months after the treatment. DISCUSSION Although the treatment of musculoskeletal disorders with the concentrate of a platelet-rich plasma (PRP) is a frequently used method, particularly in private medical practice, the scientific literature can offer just a very few studies studying in depth the use of this method of treatment in humane medicine. CONCLUSIONS Based on the results of our study, the hypothesis can be accepted that the concentrate of platelet-rich plasma administered through a series of 3 injections applied in the subacromial space in patients with shoulder impingement syndrome has positive effects on the daily activities of patients as well as on the objective evaluation via the selected scoring systems. Key words:platelet-rich plasma, shoulder impingement syndrome.
Keywords: Platelet-Rich Plasma; management bolesti; Male; Female; injekce intraartikulární; Middle Aged; Treatment Outcome; Pain Management; Injections, Intra-Articular; Pain Measurement; Shoulder Impingement Syndrome; mužské pohlaví; určení symptomu; ženské pohlaví; Glucocorticoids; Symptom Assessment; antiflogistika; měření bolesti; plazma bohatá na destičky; syndrom zhmožděného ramene; lidé středního věku; glukokortikoidy; Anti-Inflammatory Agents; výsledek terapie; lidé; Humans